Absolute roughness calculation by the friction factor calibration using the Alternative Hydraulic Gradient Iterative Method on water distribution networks - Alessandro de Araújo Bezerra; Marco Aurélio Holanda de Castro; Renata Shirley de Andrade Araújo (Revista Brasileira de Recursos Hídricos)
ABSTRACT The main objective of this research is the development of a new formulation for calibration of the head loss universal equation friction factor using the Alternative Hydraulic Gradient Iterative Method for calculating the absolute roughness. The method was applied with the aid of Epanet2.dll library for hydraulic simulations in two fictitious distribution networks. The influence of the initial roughness adopted, the number of nodes with known pressure data and position of the nodes with known pressures was tested. To test the influence of the initial roughness to be adopted a computer subroutine has been developed in order to calculate the most appropriate initial roughness for each section. The results showed that it is recommended to use as starting absolute roughness the usual value for the pipe material as new. The developed computational subroutine is recommended for unknown pipes network material or very old networks. How higher number of known pressures in the distribution network, better the accuracy of the method. However, a good layout of the nodes with known pressures was more important than a large number of pressure measurements. The best configuration found to the nodes with known pressures they were separated compared setting together with each other. The method was simple to apply and with good results, and can be applied with a small number of iterations.